Technology advancement of maintaining reservoir pressure in oil carbonate fields - Agzamov Аtabek; Аbbasova Saidakhon; Karshiev Аbdukhoshim; Razzakov Otabek; Sonaev Sanjar (E3S Web of Conferences, 2024)
In the work, based on a comprehensive analysis of geological and field information and the dynamics of technological indicators of field development, the effectiveness of the applied waterflooding system was evaluated and the results obtained were compared with the theoretical foundations of the method.The study used a set of well-known geological technological methods used in oil and gas production: mathematical modeling to establish the dependence of the oil displacement ratio by water on the permeability of the reservoir and the average annual water cut of well production from the volume of injected water; hydrodynamic calculations in determining the oil recovery factor in natural conditions; mathematical statistics to determine the accumulated oil production over the entire development period and its recovery factor; experimental studies in determining the coefficient of oil displacement by water.It is shown that: productive horizons confined to a single reef complex significantly differ in the degree of geological heterogeneity; due to the isolation of the aquifer, the natural mode of operation of productive horizons is closed-elastic with a transition to the mode of dissolved gas; the dynamics of the growth of water cut and oil production indicate an insignificant role of fracturing in the process of its extraction; a development system with areal water injection under the oil-water contact and a dense grid of production wells, where a phased transfer of sampling intervals was carried out, made it possible to more than double the oil recovery factor; the effect of waterflooding was obtained due to the achieved high values of sweep efficiency and waterflooding sweep efficiency.